The Nutritional Value of Protein-hydrolyzed Formulae. Issue 1 (2nd January 2016) - Agostoni, Carlo; Terracciano, Luigi; Varin, Elena; Fiocchi, Alessandro
Abstract : Allergy to cow's milk proteins is a challenging condition in early infancy. Allergic infants may be predisposed to impairments of growth from either the disease itself or the nutritional constraints of the exclusion diet they should follow. Formulae based on extensively hydrolyzed cow's milk proteins are widely used, representing therapy, and constituting 100% nutrient source in the first four to six months of life and half the daily nutrient intake in the second semester of life. In some cases, these products are used also for preventive purposes. Some impairments in growth have been reported for infants using these products, even if mostly limited to the first year of life, with no apparent consequences in either the medium or long term. The macronutrient content of infant formulae based on protein hydrolysates, whichever the source, should carefully be tested not only as far as the optimal utilization of nitrogenous sources but also on the nature and metabolic fate of non-nitrogen caloric sources, represented by carbohydrates and fats, and micronutrients, particularly iron. It is recommended that studies aimed at the allergologic effects of these products also include an appropriate nutritional evaluation to determine their efficiency.